Genetic basis of the early heading of high-latitude weedy rice - Li, Zhuan; Gui, Rui; Yu, Xiaoyu; Liang, Chengwei; Cui, Juan; Zhao, Xue; Zhang, Xuemin; Yu, Pengcheng; Chen, Wenfu; Sun, Jian (Frontiers in Plant Science, 2022)
Japonica rice (Oryza sativa L.) is an important staple food in high-latitude regions and is widely distributed in northern China, Japan, Korea, and Europe. However, the genetic diversity of japonica rice is relatively narrow and poorly adapted. Weedy rice (Oryza sativa f. spontanea）is semi-domesticated rice. Its headings are earlier than the accompanied japonica rice, making it a potential new genetic resource, which can make up for the defects of wild rice that are difficult to be directly applied to japonica rice improvement caused by reproductive isolation. In this study, we applied a natural population consisting of weedy rice, japonica landrace and japonica cultivar to conduct genome-wide association study of heading date and found four loci could explain the natural variation of heading date in this population. At the same time, we developed recombinant inbred lines constructed by early-heading weedy rice WR04-6 and its accompanied japonica cultivar SN265 to carry out QTL mapping analysis of the heading date and mapped four QTLs and three epistatic effect gene pairs. The major locus on chromosome 6 overlapped with the GWAS result. Further analysis found that two genes Hd1 and OsCCT22 on chromosome 6 (Locus 2 and Locus 3) may be the key points of the early-heading character of weedy rice. As minor effect genes, Dth7 and Hd16 also have genetic contributions to the early heading of weedy rice. In the process of developing the RIL population, we introduced fragments of Locus2 and Locus 3 from the weedy rice into super-high-yielding japonica rice, which successfully promoted its heading date by at least 10 days and expanded the rice suitable cultivation area to northward by about 400 km. This study successfully revealed the genetic basis of the early heading of weedy rice and provided a new idea for the genetic improvement of cultivated rice by weedy rice.